Prospects and Challenges of transforming local government into a learning organisation - Tshishonga, N. (International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa, 2018)
This paper explores the prospects and challenges of transforming local government as a learning organisation. The Local Government Turnaround Strategy (LGTAS) and local government scholars (Amtaika, 2013; Reddy & Maharaj, 2008; Tapscott, 2008; Thornhill, 2008, Tshishonga, 2015, etc.) have diagnosed the challenges facing the local sphere. The diagnosed challenges include amongst others, administrative incapacity, inefficient delivery, under spending and corruption, inadequate consultation, poor responsiveness and lack of accountability. National interventions such as Project Consolidate (2004-2006), Siyenza Manje Programme (2006-2009), Local Government Turnaround Strategy (2009), Operation Clean Audit Programme (2009-2014)and currently Back to Basics were institutionalised in order to mitigate these predicaments and their effects.Despite these interventions, local government is still in crisis and unable to fulfil its mandate. The paper argues that COGTA, SALGA and other local government stakeholders entrusted to play a meaningful and pivotal role in creating an independent and competent structure, should strive to transform local sphere into a learning organisation. Proponents of learning organisation theory such as Hudson (1995), Marquardr (2011) and Senge (1990 & 2006), view learning organisation as an organisation capable of facilitating the learning of its workforce and harnessing knowledge capability and experience for the benefit of all its stakeholders. Such learning is encouraged at individual level within teams and organisation-wide level. By employing learning organisation within the local government context, capacity and capability of all stakeholders would be optimally utilised for the development of the local sphere of government. Thus, building and transforming local government into a vibrant and competent learning organisation would require collective envisioning organisational culture,strategy and enabling structure.
Journal article published in The 3rd Annual International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: COGTA; Learning organisation; Local government; South African Local Government Association; Local government